The history of Louisa Barnes Pratt: being the autobiography of a Mormon missionary widow and pioneer - Pratt, Louisa Barnes, 1802-1880, author; Ellsworth, S. George, editor; Utah State University Press, publisher (Colorado State University. Libraries, 1998)
In her memoir, and 1870s revision of her journal and diary, Louisa Barnes Pratt tells of childhood in Massachusetts and Canada during the War of 1812, and independent career as a teacher and seamstress in New England, and her marriage to the Boston seaman Addison Pratt. Converting to the LDS Church, the Pratts moved to Nauvoo, Illinois, from where Brigham Young sent Addison on the first of the long missions to the Society Islands that would leave Louisa on her own. As a sole available parent, she hauled her children west to Winter Quarters, to Utah in 1848, to California, and, in Addison's wake.
Foreword / Maureen Ursenbach Beecher -- Introduction -- Dramatis Personae -- Author's Preface -- Part 1: On Joining the Mormons. Youth to Arrival in Salt Lake Valley, September 1848 -- Youth Memoirs, 1802 to September 1825 -- Independent Young Woman Memoirs, September 1825 to April 1831 -- The Years at Ripley, New York Memoirs, April 1831 to June 1838 -- From Ripley, New York, to Nauvoo, Illinois Memoirs, October 1838 to Fall 1841 -- Nauvoo, Missionary Widow Memoirs, Fall 1841 to Spring 1846 -- In the Exodus from Nauvoo to Salt Lake Valley Memoirs, Spring 1846 to September 1848 -- Part 2: On a Mormon Mission to Tahiti. Salt Lake Valley, September 1848 to April 1850 The Mission to the Society Islands, April 1850 to July 1852 -- In Salt Lake Valley Memoirs, September 1848 to April 1850 -- Mission Begun, Salt Lake City to Sacramento Memoirs, 7 May 1850 to July 1850 -- From San Francisco to Tubuai Journal A, Part 1, 26 July 1850 to January 1851 -- The Island Tubuai: A Missionary Family I Journal A, Part 2,January 1851 to 18 September 1851 -- The Island Tubuai: A Missionary Family II Memoirs, 15 September 1851 to 1 February 1852 -- The Islands Tubuai and Tahiti: A Missionary Family III Memoirs, February 1852 to 6 April 1852 163 13 Retreat and the Voyage Home Journal B, Part 1, 15 April 1852 to 4 July 1852 -- Part 3: On Early California. The San Bernardino Experience, 1852 to 1857 The Break-up at San Bernardino, January 1858 -- San Francisco and San Jose Journal B, Part 2, 4 July 1852 to 4 December 1852 -- San Bernardino I Memoirs, December 1852 to April 1856 -- San Bernardino II Memoirs, 14 April 1856 to 8 February 1857 -- San Bernardino III Memoirs, February 1857 to January 1858 -- Part 4: On Pioneer Living in Beaver. Beaver, Utah Territory, 1858 to 1880 -- Fateful Move: San Bernardino to Beaver, Utah Memoirs, January 1858 to January 1859 -- Settling in at Beaver Memoirs, January 1859 to July 1860 -- Beaver and a Trip to California Memoirs, July 1860 to December 1864 -- Beaver and Family Memoirs, January 1865 to December 1869 -- A Railroad Trip to East Canada Memoirs, Winter 1870-71 to December 1871 -- A Variety of Activities Memoirs, December 1871 to December 1875 -- Sunset Years at Home in Beaver Memoirs, December 1875 to August 1880.
Keywords: Mormons -- United States -- Biography; Frontier and pioneer life; Pratt, Louisa Barnes, 1802-1880